A bibliometric analysis of reverse osmosis: How influential can it be? - Syafiqah Hanis, Mohd Fauzi; Norazaliza, Mohd Jamil
Reverse osmosis is a treatment process to produce highly purified water in wastewater management. This study was designed to assess the worldwide research trends of the reverse osmosis field in terms of publication output, keywords, journals, countries, institutions, collaboration, research areas, authors, document types, and languages. A bibliometric analysis was conducted on 6,939 research articles obtained from the Web of Science (WOS) database that were published from 1970 to 2019. The bibliometric map and network were generated using VOSviewer software. Results have shown that the most related keywords are desalination and nanofiltration. The most preferred journal with 40,314 total citations was published by Elsevier. Researchers from the United States contributed the most global publications. The most productive academic institution was the National University of Singapore among 25 leading countries. The reverse osmosis topic is mostly used in Engineering and Water Resources area. The researchers from South Korea were the most productive authors in this area. The findings of this study will enable interested researchers to understand the performance of reverse osmosis research worldwide and provide recommendations for further research